Exploring the effects of intragroup conflict and past performance feedback on team effectiveness - Passos, A. M.; Caetano, A. (Journal of Managerial Psychology, 2005)
Purpose – The purpose of this paper is to test a model of the effects of intragroup conflict (relationship conflict, task conflict and process conflict), past performance feedback and perceptions of team decision?making effectiveness on team performance and affective responses. Design/methodology/approach – A sample of 183 individuals, working in 47 different teams, participated in this study. All the teams were involved in a national management challenge for a five?week period. Three questionnaires were sent directly to team members by e?mail at different times of the challenge period to collect data concerning demographic data (questionnaire 1), perceptions of team functioning (questionnaire 2) and perceptions of team decision?making effectiveness as well as the affective responses (questionnaire 3). The level of analysis in this study was the group. Thus, all individual survey responses were aggregated to the team level for statistical analysis. Findings – Results showed a full mediation effect of perceptions of team decision in the relationship between process conflict and team performance. Task and relationship conflict showed no significant relationships with team performance and satisfaction with the team. The result that effective past performance feedback directly influences team performance, in a positive way, suggests that past effective decisions may reinforce the decision?making processes previously used by team members. Research limitations/implications – One possible limitation of this study is the fact that measurements were taken at different times of the management challenge. In fact, while intragroup conflict was measured two weeks after the beginning of the challenge, the other variables were measured at the end of the challenge. This time measurement difference could raise some questions concerning the stability of the intragroup conflict over time in work teams. Future research should address this hypothesis. Future research should also elucidate the influence of contextual variables, such as cultural values, on the relationship between intragroup conflict and performance outcomes. Practical implications – This study helps managers to understand how to benefit from conflict. In a highly competitive environment, disagreement among team members about “how to do it” seems to decrease decision?making effectiveness. Originality/value – This study fills a gap in the conflict literature concerning the impact of intragroup conflict in the team members' perceptions of decision?making effectiveness and how it affects the overall performance. Moreover, this study also clarifies the importance of past performance to the actual team outcomes.